Use of Analytical Network Process Algorithm in the decision-making process. Issue 1 (June 2021) - Surya, Buyung Perdana; Sai, Laila Refiana; Jenita,; Suwarno, Suwarno; Wahab, Wirdayani; Medaline, Onny; Rusmardiana, Ana; Anriani, Stepi; Bhawika, Gita Widi; Mujanah, Siti
Abstract: The aim of this research is to implement a decision support system where the resulting system is in the form of a recommendation for existing outcomes. Conducting research to select sunblock products. Sunblock is one of the lotions that must be used before leaving the house so that the skin can be protected from sunlight and UV rays, UV rays can have a harmful effect on the skin, therefore the skin needs sunlight protection, one of which is by using a sublock, many sunblock products on the market. The aim of this study is therefore to find the best sunblock products based on the consumer experience of sunblock users. The data obtained to complete the study were taken from the results of questionnaires distributed to sunblock users randomly located in the Simalungun district. This study uses the ANP (Analytic Network Process) decision support system, the researcher uses several criteria to complete this study, including: (H) Price, (Jk) Skin Type, (Ef) Side Effects, (Kp) Product Quality, (Ap) The rules of use, (Ktp) Product affordability and alternatives used are: (A1) Nivea, (A2) Vaseline, (A3) Wardah. The results of the study using the ANP method based on a questionnaire distributed to consumers using sunblock showed that the best recommendations for sunblock type recommended by consumers were Nivea (A1) = 7.2, Vaseline (A2) = 5.4 and Wardah (A3) = 5.07.